Tcf1 Sustains the Expression of Multiple Regulators in Promoting Early Natural Killer Cell Development - Liu, Juanjuan; Wang, Zhao; Hao, Shanshan; Wang, Fang; Yao, Yingpeng; Zhang, Yajiao; Zhao, Yanyi; Guo, Wenhui; Yu, Guotao; Ma, Xiaohan; Liu, Jingjing; Chen, Feng; et al. (Frontiers in Immunology, 2021)
T cell factor 1 (Tcf1) is known as a critical mediator for natural killer (NK) cell development and terminal maturation. However, its essential targets and precise mechanisms involved in early NK progenitors (NKP) are not well clarified. To investigate the role of Tcf1 in NK cells at distinct developmental phases, we employed three kinds of genetic mouse models, including Tcf7fl/flVavCre/+, Tcf7fl/flCD122Cre/+ and Tcf7fl/flNcr1Cre/+ mice, respectively. Similar to Tcf1 germline knockout mice, we found notably diminished cell number and defective development in BM NK cells from all strains. In contrast, Tcf7fl/flNcr1Cre/+ mice exhibited modest defects in splenic NK cells compared with those in other two strains. Combined analysis of the existing ATAC-seq and ChIP-seq data, we found that Tcf1 directly targeted 110 NK-related genes which displayed differential accessibility in absence of Tcf1. Along with this clue, we further confirmed that a series of essential regulators were expressed aberrantly in distinct BM NK subsets with conditional ablating Tcf1 at NKP stage. Eomes, Ets1, Gata3, Ikzf1, Ikzf2, Nfil3, Runx3, Sh2d1a, Slamf6, Tbx21, Tox, and Zeb2 were downregulated, whereas Spi1 and Gzmb were upregulated in distinct NK subsets due to Tcf1 deficiency. The dysregulation of these genes jointly caused severe defects in NK cells lacking Tcf1. Thus, our study identified essential targets of Tcf1 in NK cells, providing new insights into Tcf1-dependent regulatory programs in step-wise governing NK cell development.